2021
DOI: 10.1111/sltb.12775
|View full text |Cite
|
Sign up to set email alerts
|

Thwarted belongingness predicts greater neural reactivity to a novel social exclusion image set: Evidence from the late positive potential

Abstract: Introduction: Thwarted belongingness (TB) is among the most well-researched risk factors for suicidal ideation (SI). Yet, there is little research examining neural mechanisms underlying this construct. The present study used a novel social exclusion image set in concert with the late positive potential (LPP) to test the role of neural reactivity social exclusion in TB and SI.Methods: Participants (n = 243) were recruited based on elevated suicide risk and completed an emotional picture viewing task. The LPP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…At the same time, researchers believe that individuals who are excluded from a group due to various reasons may experience a lack of interpersonal relationships, which can have negative impacts on them (Zhou, 2004). Particularly, individuals who are sensitive to interpersonal relationships perceive higher levels of exclusion, which can strengthen their suicidal ideation (Albanese et al, 2021). The interpersonal theory of suicide suggests that when individuals experience thwarted belongingness and perceived burdensomeness, they develop suicidal ideation.…”
Section: Social Exclusion and Suicidal Ideationmentioning
confidence: 99%
“…At the same time, researchers believe that individuals who are excluded from a group due to various reasons may experience a lack of interpersonal relationships, which can have negative impacts on them (Zhou, 2004). Particularly, individuals who are sensitive to interpersonal relationships perceive higher levels of exclusion, which can strengthen their suicidal ideation (Albanese et al, 2021). The interpersonal theory of suicide suggests that when individuals experience thwarted belongingness and perceived burdensomeness, they develop suicidal ideation.…”
Section: Social Exclusion and Suicidal Ideationmentioning
confidence: 99%
“…Individuals who perceived higher levels of NSE may view these events as evidence that they do not belong, thus increasing risk of SI (Blais et al , 2021). Studies have also demonstrated that NSE such as social exclusion are directly related to thwarted belongingness, and indirectly to SI through thwarted belongingness (Albanese et al , 2021). As previously noted, regarding NSE and perceived burdensomeness, few studies have directly examined the relationship between NSE, SI and thwarted belongingness.…”
Section: The Interpersonal Theory Of Suicidementioning
confidence: 99%
“…It significantly positively predicts depression and a greater neural response to new social exclusion. 23,24 According to the theory of interpersonal relationships, interpersonal problems have a significant impact on the onset and persistence of depression. 25,26 Thwarted belongingness reflects disharmony in an individual's interpersonal relationships, affects the individual's psychological and social adjustment, and further increases the risk of depression.…”
Section: The Mediating Role Of Thwarted Belongingness Between Social ...mentioning
confidence: 99%